ANALISIS SISTEM MANAJEMEN BERBASIS TEKNOLOGI INFORMASI DALAM MENINGKATKAN MUTU OUTPUT PESERTA DIDIK DI MI NURUL HUDA SIDOARJO - S. Subaidah; Nadlir Nadlir (Primary School Teacher Education, Universitas Nahdlatul Ulama Sidoarjo, 2023)
Madrasah Ibtidaiyah (MI) Nurul Huda must provide quality education services and be supported by information technology in improving academic and non-academic quality. This study aims to determine information technology-based management systems at MI Nurul Huda and to analyze information technology-based management systems in improving the quality of student output at MI Nurul Huda. This research uses a descriptive qualitative method. Data collection techniques used are interviews, observation, and documentation. The data analysis technique used is data reduction, data display, and conclusion drawing. The subjects in this study were the principal, the vice principal, and the teacher council. Based on the results of this study it can be concluded that the information technology management system that takes place at MI Nurul Huda is computer-based learning, E-Learning, data-based applications, E-Rapot, Fingerprint, PPDB Online, and also webinars; efforts made by madrasas to improve the quality of output at MI Nurul Huda include: organizing digital-based learning activities during the Covid-19 pandemic and carrying out face-to-face learning assisted by technology, although it is still limited to improving the quality of teaching and learning; sending talented students to take part in academic and non-academic competitions, motivating students, and providing directions to students who wish to continue to a higher level, the use of information technology can make a significant contribution in improving the quality of student output both in data management students, the learning process, a collaboration between teachers, students, and parents.